Factors Impacting Students’ Learning Performance in Higher Education in Chengdu, China - Xu, Peijuan (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: The effectiveness of education has always been a focus of social attention. Previous research has mostly focused on the level of education in primary and secondary schools, and some studies have shown that college students may have different motivations and learning concepts. Therefore, this study aims to take Xihua University in Chengdu, China as an example to systematically examine various factors that affect the academic performance of university students. Through quantitative analysis, this study investigated the impact of five independent variables (learning attitude, learning anxiety, learning motivation, teacher ability, and student participation) on the dependent variable (academic performance), especially in higher education. Moreover, it aims to identify significant differences between variables. Methodology: Research Design, Data, and Methods: This study used the Project Objective Consistency Index (IOC) to test the validity of the questionnaire, and Cronbach's Alpha was used as reliability in the pilot study (n=30). They used the multiple linear regression method to analyze the effective responses of 80 students at Xihua University and verify the significant relationship between variables. Afterward, a group of 30 students underwent a 14-week planned study. Then, the quantitative results after and before the scheduled study were compared in paired sample t-tests. Results: In multiple linear regression, studies have shown that learning attitude, learning anxiety, learning motivation, teacher ability, and student participation have a significant impact on student academic performance. Finally, the comparison results of paired sample t-tests indicate substantial differences in student academic performance between the post-strategic and pre-strategic plan stages. Conclusion: This research endeavors to foster students' learning performance in the context of Chengdu, China.